(untitled) (Педагогіка вищої та середньої школи, 2007)
Clause is devoted to a substantiation of internal logic talented and deeply of various versions of performance Gould and Devetci, proceeding from given of stylistics Mozart of epoch of connection of bases Viennese classicism with updated aspiration to a barocco heritage I.S. Bach and it o f the sons, is especial as I.C. Bach.